Firm efficiency and corporate performance : The moderating role of controlling shareholders - Nguyen, Thien Huu; Asif, Jawad; Kweh, Qian Long; Ting, Irene Wei Kiong (Emerald Publishing, 2023)
This study analyses the effects of firm efficiency on firm performance and how controlling shareholders moderate the link between the two variables. Design/methodology/approach: This study employs data envelopment analysis to estimate firm efficiency and the panel regression method to assess the hypothesised relationships among 1,295 firm-year observations of publicly listed firms in Malaysia from 2015 to 2019. Findings: The results indicate that firm efficiency (technical efficiency, pure technical efficiency and scale efficiency) has mixed relationships with firm performance (return on assets, market-to-book ratio and operating cash flows), all of which are being moderated by controlling shareholdings. Practical implications: This study highlights the importance of assessing firm efficiency as the key success factor for improving firm performance. Industrial managers should manage efficiently their resources or operating costs in achieving their corporate financial goals. Moreover, this study notes the presence of controlling shareholders, who can be either self-interested or company goal aligned. Originality/value: This study suggests becoming efficient in transforming inputs into outputs is a prerequisite before investigating accrual-based and cash-based firm performance measures, and the presence of controlling shareholders matters in these regards.